2020
DOI: 10.3390/ijerph17249511
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory, Metabolic and Muscular Responses during a Video-Recorded Aerobic Dance Session on an Air Dissipation Platform

Abstract: Background: Aerobic dance (AD) is an appropriate physical activity for improving cardiorespiratory fitness. This study aimed to compare cardiorespiratory and metabolic responses, and muscle fatigue between an air dissipation platform (ADP) and a hard surface during a video-recorded AD session. Methods: 25 healthy young women (23.3 ± 2.5 years) completed three sessions. In session 1, participants performed an incremental test to exhaustion on a treadmill. One week after session 1, participants were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…One of the purposes of this study was to be able to control exercise intensity on an ADP. Our previous findings demonstrated that exercise on an ADP stimulates a greater cardiorespiratory and metabolic response compared to exercise on a hard surface [35]. The exercise intensity of the sessions was controlled using the Borg scale of 0 to 10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the purposes of this study was to be able to control exercise intensity on an ADP. Our previous findings demonstrated that exercise on an ADP stimulates a greater cardiorespiratory and metabolic response compared to exercise on a hard surface [35]. The exercise intensity of the sessions was controlled using the Borg scale of 0 to 10.…”
Section: Discussionmentioning
confidence: 99%
“…Unstable surfaces have been shown to be a suitable alternative for improving cardiorespiratory fitness and producing positive changes in body composition in overweight women [32]. In addition, several studies have shown that exercise performed on unstable surfaces can be more intense compared to exercise on the ground [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent contributions from our research group have determined that the execution surface in AD activities can influence cardiorespiratory and metabolic responses. Unstable surfaces with a higher elastic component, such as an air dissipation platform (ADP), could increase the blood lactate concentration (~6 mmol·L −1 ) and cardioventilatory response during an AD session higher than on hard surfaces [ 26 ]. This increase in acute cardioventilatory and metabolic responses after the ADP session can be due to a decline in the damping-induced impact forces and an enhance in instability and contact times.…”
Section: Introductionmentioning
confidence: 99%
“…A steady state of and blood lactate concentration, as well as an adequate ventilatory efficiency with a low blood lactate concentration (~2.7 mmol·L −1 ), has been observed at a load intensity of the LT or the VT1 in predominantly aerobic metabolism (2, 9, 10, and 17). However, higher cardioventilatory responses and blood lactate concentrations (~6 mmol·L −1 ) have been verified in an AD session on an ADP compared to a hard surface [ 26 ]. Given the differences observed between several exercise modes, the treadmill, and various types of AD, it is plausible to propose that AD session on an ADP could condition the kinetics of by increasing the and decreasing ventilatory efficiency to a greater extent than a treadmill test at an intensity of VT1 (~3 mmol·L −1 ), in which aerobic metabolism predominates.…”
Section: Introductionmentioning
confidence: 99%